ANALISIS KEUNGGULAN KOMPARATIF USAHATANI PADI ORGANIK DI DESA SUKOREJO KECAMATAN SAMBIREJO KABUPATEN SRAGEN - Siregar, Duwi Majida Hayati; Suhartini; Widyawati, Wiwit (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
The agricultural sector that has the potential to be competitive, one of which is the food crop in rice commodities (Oryzae sativa) because rice is a leading commodity and the main food commodity in Indonesia. Indonesia can increase the competitiveness of rice with the emergence of "Go Organic", which is organic rice which is expected to be able to be competitive in the domestic and international markets. Therefore, this paper aims to analyze the income of organic rice farming businesses and analyze the comparative advantages of organic rice farming in Sukorejo Village, Sambirejo District, Sragen Regency. The location determination method in this study was carried out intentionally (purposively) in Sukorejo Village, Sambirejo District, Sragen Regency. The study was conducted in October 2022. In this study, the determination of the number of samples using the slovin formula was known that the number of samples was 67 organic rice farmers. The data analysis method used in this study is income analysis and Domestic Resource Cost (DRC) analysis to calculate the comparative advantages of organic rice farming. The results showed that (1) the income of organic rice farming in Sukorejo Village, Sambirejo District, Sragen Regency is profitable because (TR>TC) is Rp. 24.049.786 per hectare in one planting period (July-October 2022), (2) organic rice farming has a comparative advantage with a DRCR value of 0.35. The DRCR value of less than one means that organic rice in Sukorejo Village, Sambirejo District, Sragen Regency is efficiently produced domestically because it is more profitable than importing.